2016
DOI: 10.1155/2016/5789232
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Effects of Xylooligosaccharides on the Improvement of Microbiota Balance in Human Subjects

Abstract: It has been indicated that probiotics can be nourished by consuming prebiotics in order to function more efficiently, allowing the bacteria to stay within a healthy balance. In this study, we investigated the effects of xylooligosaccharides- (XOS-) enriched rice porridge consumption on the ecosystem in the intestinal tract of human subjects. Twenty healthy subjects participated in this 6-week trial, in which 10 subjects received XOS-enriched rice porridge while the others received placebo rice porridge. Fecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 27 publications
4
46
1
Order By: Relevance
“…The bifidogenic effects of XOS on B. lactis seemed to be more efficient than those of FOS alone in a colon model, suggesting that the association between XOS and B.lactis could generate a successful symbiotic product [64]. A 6-week randomized controlled trial, conducted on 20 healthy subjects, demonstrated that those who consumed 150 g rice porridge with XOS supplementation (1.2 g XOS once daily) had increased fecal bacterial counts of Lactobacilli and Bifidobacterium and a decreased Clostridium, without altered total anaerobic bacterial counts, compared to the control group, who ate only rice porridge, without supplementation [65]. The increase in lactobacilli was in contrast with the above results obtained in a pure culture [63] and with another study, conducted on humans by Finegold et al, where the authors showed no changes in lactobacilli counts, stool pH and SCFA production after XOS administration at different doses (1.4 g and 2.8 g) [66].…”
Section: New Molecules With Prebiotic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bifidogenic effects of XOS on B. lactis seemed to be more efficient than those of FOS alone in a colon model, suggesting that the association between XOS and B.lactis could generate a successful symbiotic product [64]. A 6-week randomized controlled trial, conducted on 20 healthy subjects, demonstrated that those who consumed 150 g rice porridge with XOS supplementation (1.2 g XOS once daily) had increased fecal bacterial counts of Lactobacilli and Bifidobacterium and a decreased Clostridium, without altered total anaerobic bacterial counts, compared to the control group, who ate only rice porridge, without supplementation [65]. The increase in lactobacilli was in contrast with the above results obtained in a pure culture [63] and with another study, conducted on humans by Finegold et al, where the authors showed no changes in lactobacilli counts, stool pH and SCFA production after XOS administration at different doses (1.4 g and 2.8 g) [66].…”
Section: New Molecules With Prebiotic Effectsmentioning
confidence: 99%
“…↑ Bifidobacteria (especially Bifidobacterium lactis and Bifidobacterium adolescentis [63]), Lactobacilli [65] and butyrate fecal concentrations [62]. ↓ Clostridium growth [65]. No changes in lactobacilli counts, stool pH and SCFAs production [66].…”
Section: Xilooligosaccharides (Xos)mentioning
confidence: 99%
“…Fructo‐oligosaccharides (FOS), a dietary fibre rich in fruits and vegetables, were added to improve blood glucose homeostasis in animal models (Lin et al . 2016). Oligoxylose has the function of prebiotics.…”
Section: Treatment and Adjustmentmentioning
confidence: 99%
“…Moreover, the extracted hemicelluloses exhibit longer chain lengths compared to the low molecular weight hemicellulose obtained from the steeping lye. Because oligomeric sugar containing lyes are of special interest in a biorefinery context, where they are further processed, e.g., into xylooligosaccharides for prebiotic formulations [34,35], a co-product of higher market value can be separated by the described process.…”
Section: Process Viabilitymentioning
confidence: 99%